Self‐perceived gait quality in young adults with cerebral palsy. (12th March 2020) - Bonnefoy‐Mazure, Alice; De Coulon, Geraldo; Armand, Stephane
Abstract : Aim: To explore how patients with cerebral palsy (CP) perceive their gait and evaluate associations between subjective gait perception and: objective gait parameters, endurance, pain, and fatigue. Method: Sixty‐two patients (21 females and 41 males; mean [SD] age 20y [5y 1mo], range 15–29y) performed a clinical gait analysis. Self‐selected walking speed, Gait Profile Score, and Gait Variable Score were calculated. Subjective gait perception was assessed with a visual analogue scale using the question: 'On a scale from 0 (worst) to 10 (optimal), how would you describe your walking today?'. A 6‐minute walk test (6MWT) measured endurance; the 36‐Item Short Form Health Survey (SF‐36) evaluated quality of life. T ‐tests, Pearson correlations, and univariate and multiple linear regression models were used to compare and find associations between the data. Results: Overall mean (SD) subjective gait perception was 7.5 (1.8) and was significantly higher for patients in Gross Motor Function Classification System (GMFCS) level I (7.9 [1.5]) than for patients in GMFCS levels II and III (5.9 [2.0]). Positive correlations were found between subjective gait perception and gait scores, walking speed, 6MWT distance, and SF‐36 score. Only walking speed was a significant predictor of subjective gait perception. Interpretation: Subjective gait perception was influenced by GMFCS level and linked partially with the walking speed. The gait quality did not explain subjective gait perception. It is important to combine subjective and objective gait scores to develop personalized therapeutic goals. What this paper adds: Subjective gait perception is influenced by the physical impairment levels of patients with cerebral palsy. Subjective gait perception and objective gait scores are associated. Walking speed is the only predictor of gait perception. What this paper adds: Subjective gait perception is influenced by the physical impairment levels of patients with cerebral palsy. Subjective gait perception and objective gait scores are associated. Walking speed is the only predictor of gait perception. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Autopercepción de la calidad de la marcha en adultos jóvenes con parálisis cerebral Objetivo: Explorar cómo los pacientes con parálisis cerebral (PC) perciben su marcha y evaluar las asociaciones entre la percepción subjetiva de la marcha y los parámetros objetivos de la marcha, su resistencia, dolor y fatiga. Método: Sesenta y dos pacientes (21 mujeres y 41 varones; media [DE] edad 20 años [5 años 1m], rango 15‐29 años) realizaron un análisis clínico de la marcha. Se calcularon la velocidad de marcha auto‐seleccionada, la puntuación del perfil de la marcha y la puntuación variable de la marcha. La percepción subjetiva de la marcha se evaluó con una escala analógica visual utilizando la pregunta: "En una escala de 0 (peor) a 10 (óptima), ¿cómo describirías tu caminar hoy?". Una prueba de caminata de 6 minutos (6MWT, siglas en inglés) midió la resistencia; La Encuesta de Formato Corto de Salud de 36 elementos (SF‐36, siglas en inglés) evaluó la calidad de vida. Se utilizaron pruebas T, correlaciones de Pearson y modelos de regresión lineal univariada y múltiple para comparar y encontrar asociaciones entre los datos. Resultados: La percepción de la marcha subjetiva media general (DE) fue de 7, 5 (1, 8) y fue significativamente mayor para los pacientes en el nivel I del Sistema de Clasificación de la Función Motora Gruesa (GMFCS) (7, 9 [1, 5]) que para los pacientes en los niveles II y III de GMFCS (5, 9 [2, 0 ]). Se encontraron correlaciones positivas entre la percepción subjetiva de la marcha y las puntuaciones de la marcha, la velocidad de marcha, la distancia de 6MWT y la puntuación SF‐36. Solo la velocidad al caminar fue un predictor significativo de la percepción subjetiva de la marcha. Interpretación: La percepción subjetiva de la marcha estuvo influenciada por el nivel de GMFCS y se relacionó parcialmente con la velocidad de la marcha. La calidad de la marcha no explicaba la percepción subjetiva de la misma. Es importante combinar puntajes de marcha subjetivos y objetivos para desarrollar metas terapéuticas personalizadas. Resumo: Qualidade auto‐percebida da marcha em jovens adultos com paralisia cerebral Objetivo: Explorar como pacientes com paralisia cerebral (PC) percebem sua marcha, e avaliar associações entre percepção subjetiva da marcha e: parâmetros objetivos da marcha, resistência, dor e fadiga. Método: Sessenta e dois pacientes (21 do sexo feminino e 41 do sexo masculino; média [DP] de idade 20a [5a 1m], variação 15–29a) realizaram uma análise de marcha clínica. A velocidade da marcha auto‐selecionada, Pontuação no Perfil da Marcha, e Pontuação da Variável da marcha foram calculados. A percepção subjetiva da marcha foi avaliada com uma escala visual analógica usando a questão: 'Em uma escala de 0 (pior) a 10 (ótima), como você descreveria sua marcha hoje?'. Um teste de caminhada de 6 minutos (TC6) mensurou a resistência; o Questionário de Saúde Formulário Curto com 36 itens (SF‐36) avaliou a qualidade de vida. Testes‐t, correlações de Pearson, e modelos de regressão linear univariada e múltipla foram usados para comparar e encontrar associações entre os dados. Resultados: Em geral, a média (DP) da percepção subjetiva da marcha foi 7, 5 (1, 8), e foi significativamente mais alta em pacientes com Sistema de Classificação da Função Motora Grossa (GMFCS) nível I (7, 9 [1, 5]) no que nos pacientes nos níveis GMFCS II e III (5, 9 [2, 0]). Correlações positivas foram encontradas entre a percepção subjetiva da marcha e os escores da marcha, velocidade da marcha, distância no TC6 e pontuação SF‐36. Apenas a velocidade da marcha foi preditor significativo da percepção subjetiva da marcha. Interpretação: A percepção subjetiva da marcha foi influenciada pelo nível GMFCS e parcialmente relacionada com a velocidade da marcha. A qualidade da marcha não explicou a percepção subjetiva da marcha. É importante combinar pontuações subjetivas e objetivas da marcha para desenvolver objetivos terapêuticos personalizados.